2018
DOI: 10.1017/s1047951118000434
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular mass of persistent masked hypertension in Hong Kong Chinese adolescents: a 4-year follow-up study

Abstract: Persistent masked hypertension in adolescents is associated with elevated left ventricular mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…High BP in children and adolescents is defined at or above the 95 th percentile of the distribution, and high normal BP is defined by the upper 10% of the distribution. In the future, long-term studies should be conducted to explore clinical markers for early cardiovascular disease that include increased carotid intimamedia thickness, left ventricular mass and pulse wave velocity, flow-mediated dilatation, retinal vascular narrowing, or increased cardiovascular biomarkers (interleukin-6, fibrinogen, and so on) [37][38][39], which would be useful for the establishment of HBP definition in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…High BP in children and adolescents is defined at or above the 95 th percentile of the distribution, and high normal BP is defined by the upper 10% of the distribution. In the future, long-term studies should be conducted to explore clinical markers for early cardiovascular disease that include increased carotid intimamedia thickness, left ventricular mass and pulse wave velocity, flow-mediated dilatation, retinal vascular narrowing, or increased cardiovascular biomarkers (interleukin-6, fibrinogen, and so on) [37][38][39], which would be useful for the establishment of HBP definition in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Two pediatric studies reported data on persistence of masked hypertension during 4 years of follow up. Both highlight the presence of masked hypertension as significant prognostic factor for higher LVMI during follow-up compared to normotensive children [ 3 , 77 ]. Lurbe et al found that LVH at the end of follow-up period was only present in the persistent masked hypertension group or in patients with masked hypertension who progressed to sustained (true, ambulatory) hypertension (30% versus 0%; P = 0.01) compared to normotensive controls [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies reported differences in LVMI between MH (n=480) and normotensive (n=1301) children. 37–48 In all studies, LVMI was greater in MH (pooled mean=35.77 g/m 2.7 ; [95% CI, 31.96–39.57]) versus normotensive participants (pooled mean=31.28 g/m 2.7 ; [95% CI, 28.09–34.47]), with a mean difference of 3.86 g/m 2.7 ([95% CI, 2.51–5.22]; grade certainty: moderate; Figure 2). In the 6 studies analyzing the general pediatric population, LVMI of the MH participants (n=154; pooled mean=30.91 g/m 2.7 ) was greater than the normotensive participants (n=797; pooled mean=28.12 g/m 2.7 ) with a mean difference of 2.79 g/m 2.7 ([95% CI, 2.21–3.37]).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies reported differences in LVMI between MH (n=480) and normotensive (n=1301) children. [37][38][39][40][41][42][43][44][45][46][47][48] In all 2). In the 6 studies analyzing the general pediatric population, LVMI of the MH participants (n=154; pooled mean=30.91 g/m 2.7 ) was greater than the normotensive participants (n=797; pooled mean=28.12 g/m 2.7 ) with a mean difference of 2.79 g/m 2.7 ([95% CI, 2.21-3.37]).…”
Section: Subclinical Cardiovascular Outcomesmentioning
confidence: 99%
See 1 more Smart Citation